Some Biogenic Amines In The Prawn Haemolymph During Ovarian Growth And Their Effects On Vitellin Biosynthesis In The Penaeid Prawn, Penaeus Mergueinsis, Deman - Chong, Huey bing (2000)
A study on the biogenic amines in the haemolymph of penaeid prawn, Penaeus merguiensis, at different stages of ovarian growth was conducted. The gonadosomatic index (GSI) was used to show the stages of the ovarian growth. The qualitative and quantitative determination of the biogenic amines were accomplished by using the high performance liquid chromatography with electrochemical detection (HPLC-ECD) method, which provides a high sensitivity and selectivity in determining the biogenic amines. The biogenic amines can be detected at the picogram levels using this method.